Physiological and Pathological Alterations in the Mammary Gland of Holstein Cows during Transition Period - Ramos, Jean Silva; Madureira, Karina Medici; Baldacim, Vinicius Alvim Passos; da Costa e Silva, Cynthia Pereira; Dias, Mailson Rennan Borges; Stricagnolo, Cláudia Regina; Gomes, Viviani (Acta Scientiae Veterinariae, 2020)
Background: Physiological and immunological adaptations occurred in peripartum period may be responsible for susceptibility to intramammary infections during colostrogenesis. Increase in blood flow and hormones cause physiological edema by accumulation of lymphatic fluid in interstitial space. Specific composition of mammary secretion increases the susceptibility to mastitis. So, the study of physical, cellular and microbiological changes in the mammary gland in this period are fundamental for understanding, diagnosing and adopting prophylactic measures for bovine mastitis. This study aimed to characterize physiological and pathological changes that occur in the mammary gland during transition period. Materials, Methods & Results: Thirteen cows, in second to fourth lactation were followed from 3 weeks pre-calving to 3 weeks post-calving. Cows were submitted weekly to physical examination of mammary gland, strip cup test, California Mastitis Test (CMT), Microscopic Somatic Cell Count (MSCC), and bacteriological examination of mammary secretion. Mammary quarters were divided into two groups: BAC-: samples that did not present bacteriological growth throughout transition period; BAC+: samples that presented bacteriological growth in at least two isolates of the same bacterial genus. Regarding physical examination of mammary gland, the parameters localized or generalized alteration in volume, asymmetry, reddish color, reduced skin elasticity, increased temperature, and swollen consistency presented higher frequencies in the BAC- group. On the other hand, infection in mammary quarters of cows from BAC+ group promoted a decrease in frequencies of increased volume, decreased elasticity, and elevated temperature in the mammary gland, in addition to a higher positivity to CMT and higher cellularity. Overall rate of intramammary infection was 25.82%, with non-aureus Staphylococci (NAS) being the predominant agent (69.2%). Maximum peak of bacterial isolates occurred immediately after calving (33.3%). Differences were observed between groups (P = 0.021) for CMT, showing a higher frequency of positive tests in BAC+ group (36.5%) compared to BAC- group (18%). MSCC varied between weeks (P = 0.001), groups (P = 0.001), and between the interaction of the two variables (P = 0.019). Highest median value of MSCC was observed at calving (1.5 × 106 cells/mL), being different (P = 0.001) from the +1, +2, and +3 weeks and the lowest median value of MSCC (0.08×106 cells/mL) was observed in +3 compared to previous weeks (P < 0.05). Discussion: NAS was predominantly isolated in mammary secretions of cows during peripartum, it is commonly found in the skin and canal of the teat and are associated with subclinical mastitis. Peak of mammary infection was observed on calving, probably by the cortisol peak resulting in a stress leucogram and decrease in the functional activity of immune cells. Changes observed in the physical examination of mammary gland of cows from BAC- group are compatible with physiological edema caused by circulatory changes that occurs with the proximity of calving, increasing blood flow necessary for production of colostrum. Alterations in the mammary quarters of cows from BAC+ group may be associated with functional loss of mammary parenchyma or persistent infectious process, characterizing clinical findings of pathological changes during transition period. Mammary quarters of the BAC+ group presented higher percentages of positive reactions to CMT in weeks +1 and +2, and higher MSCC values and are associated with infection of the mammary gland.